Are we ready to replace physical mock exam with an online mock exam? a survey-based comparison - Sabnis, Chaitanya; Patil, Abhijit; Singh, Abhishek; Ganpule, Arvind (International Journal of Research in Medical Sciences, 2024)
Background: Mock exams have become an integral part of urology training, presently conducted in a real classroom (physical mock exam- PME). We conducted a mock exam in a virtual classroom (online mock exam- OME) for 130 urology residents. A survey was conducted to compare OME and PME. Methods: Questionnaire was developed, consisting of 16 questions, of which two question were matrix, others had options. For the matrix questions the candidates had to rate the components of the PME and OME on a scale of 1 to 5. Results: Out of the 130, 103 (86.55%) were eligible for analysis. Regarding, ease of understanding the question and fulfilling the expectations both modalities were rated highly (95.15% versus 93.2%, p=0.552 and 89.32 versus 83.5%, p=0.221). OME fared better than PME, with regards to the questions addressing; ease of understanding the explanation (p=0.000), fluency of interaction (p=0.000), ability to concentrate (p=0.002), feeling of involvement (p=0.000), logistic convenience (p=0.001), ability to network and ability to balance commitments (p=0.000). PME was superior in interacting with peers (p=0.000), and peer motivation helping them concentrate better (p=0.001). Out of the 103 respondents 79 (66.39%) recommended an OME for future. Conclusions: Online platform can be effectively used to conduct a mock exam. It is not only noninferior to PME but also has many advantages. This survey shows OME has a potential to replace PME.